Biosynthesis of lactosylfructoside by an intracellular levansucrase from Bacillus methylotrophicus SK 21.002. (12th January 2015) - Wu, Chao; Zhang, Tao; Mu, Wanmeng; Miao, Ming; Jiang, Bo
Graphical abstract: Highlights: A novel levansucrase producing strain was used to synthesize lactosylfructoside. The biosynthesized product was purified by a HPLC system for NMR analysis. The biosynthesis conditions of lactosylfructoside were optimized. Abstract: Lactosylfructoside is a functional oligosaccharide consisting ofd -glucose, d -galactose, andd -fructose. In this work, lactosylfructoside was biosynthesized from sucrose as a fructosyl donor and lactose as an acceptor by an intracellular levansucrase derived from strain Bacillus methylotrophicus ( B. methylotrophicus ) SK21.002. The trisaccharide was purified from the product using a high performance liquid chromatography (HPLC) system and was confirmed to be lactosylfructoside by nuclear magnetic resonance (NMR) spectroscopy. The biosynthesis conditions (such as pH, temperature, enzyme dosage, substrate concentrations, and the concentration ratio of the two substrates) for lactosylfructoside production were optimized. The optimum conditions for lactosylfructoside preparation were a pH of 6.5, temperature of 37 °C, and enzyme dosage of 8 U/g substrates. The concentration of substrates (total lactose and sucrose) was 400 mg/mL, and the ratio of lactose to sucrose was 1:1. The optimum time for lactosylfructoside production was 20 h, the yield of lactosylfructoside under the optimal conditions was 143 mg/mL, and the lactosylfructoside conversion efficiency was 36%.